2016
DOI: 10.1186/s40066-016-0068-2
|View full text |Cite
|
Sign up to set email alerts
|

Agrobiodiversity conservation enhances food security in subsistence-based farming systems of Eastern Kenya

Abstract: Background: Globally, there is great concern about expanding agricultural activities due to their impact in the conservation of agrobiodiversity. African continent is known for its richness in biodiversity. In Kenya, there is a continuous unabated expansion of agriculture into natural habitats due to demographic and economic pressures posing a significant threat to biodiversity. Therefore, there is a need to study biodiversity loss and its regain through practices in agricultural landscapes. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…Since then, BORA remained both a dominant and an expensive landrace in Sire District. Similarly, the dominance of few varieties in response to market demands has been reported by Mburu et al, 37 in eastern part of Kenya; leading to low common bean diversity that these authors recorded in the area. Major common bean landrace market flow is commonly found at sub-district and or district levels, but considerable informal trade also takes place across neighbors of different districts.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Since then, BORA remained both a dominant and an expensive landrace in Sire District. Similarly, the dominance of few varieties in response to market demands has been reported by Mburu et al, 37 in eastern part of Kenya; leading to low common bean diversity that these authors recorded in the area. Major common bean landrace market flow is commonly found at sub-district and or district levels, but considerable informal trade also takes place across neighbors of different districts.…”
Section: Discussionsupporting
confidence: 56%
“…36 They grow local varieties with no or little inputs and are well adapted to local climatic conditions, which may account for the high dominance of the local farmers' varieties. 37 Hence, crop diversity increased with the number of years a farmer had been engaged in farming activities in a traditional farming system. 38 A low level of diversity was detected in the collections of common bean landraces from Boloso Sore District where only two landraces were recovered revealing cases where few common bean landraces dominate.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of a food diversification policy needs appropriate strategies. Various strategies related to diversification of food consumption that can be implemented (Mburu, Koskey and Kimiti 2016) include: (i) Diversification of household businesses is directed toward increasing the income of producers, especially farmers, ranchers and small fishermen through the development of integrated farming; (ii) Diversification of business or food production and diversification of food consumption are carried out through the development of diversified integrated farming in the fields of food, plantations, animal husbandry, fisheries; (iii) Development of local food in accordance with regional wisdom and uniqueness to increase local food diversification; (iv) Human resource development in the field of food and nutrition is carried out through education, training and counseling in a more comprehensive manner. This study applies point no (iii).…”
Section: Discussionmentioning
confidence: 99%
“…Agroecosystem characteristic is one of the factors that may create a spatial variation of household food insecurity [20]. A study from Kenya indicated that households from lower midland zones with high crop diversity were more food secure compared with those from the upper midland zones with low crop diversity [21].…”
Section: Open Accessmentioning
confidence: 99%